Relationship between Corrosion of Reinforcement and Surface Cracking Width in Concrete - Jian Cao; Liangfang Liu; Shangchuan Zhao (Advances in Civil Engineering)
The durability of structure cannot be guaranteed when a corrosion expansion crack reaches the surface of the reinforced concrete member. In this paper, firstly, based on the existing theoretical model of steel corrosion degree, the calculation process of the model and the determination of the relevant parameters in the model were analyzed and discussed. Secondly, the stiffness reduction factor of concrete in the model was calculated according to the existing experimental data, and the engineering formula of the steel corrosion degree was established, which was related to the surface crack width of reinforced concrete. Moreover, the experiments of steel bar corrosion were carried out with different components of surface crack width, in which the parameters of the bar diameter, concrete protection layer thickness, and water-cement ratio were taken into consideration. The experimental phenomena and results were further analyzed and discussed. Finally, comparing with the experimental data, the engineering formula presented in the paper was validated. The results show that the calculated values by the engineering formula are in better agreement with the experimental values than those by the existing model, which provide a theoretical basis for further study on the durability limit state of the structure.